Internet access using encrypted membercard / Muhammad Syafiq Sopian - Sopian, Muhammad Syafiq (2021)
Cybercafe is popular to some people because it provides public accessibility with high specification equipment provided by the entrepreneur. The cybercafé use token system to generate user id and password by purchasing token according to the hours of use. It brings many disbenefit to the user in term of time consuming, security and availability of equipment. Therefore, the system based on token ring topology controlled by software makes the maintenance difficult by configuring wire and pc. The solution to this problem is to use encrypted member card to access internet by using captive Wi-Fi portal of Arduino ESP8266.This system is developed in Arduino ESP8266 by using C++ languages and Arduino platform. The main function of this device is to control input user of client and to also encrypt it with AES algorithm. User need to input the data using barcode scanner that contain ID and password of user. The server is controlled by PHP and MySQL database. The server includes user database and pc information. Manager can manage user and pc information if there in increasing or decreasing number of user and pc. It is connected to Arduino device.